Altered emotional experiences attributed to antipsychotic medications – A potential link with estimated dopamine D2 receptor occupancy. (28th February 2016) - Lako, Irene M.; Taxis, Katja; van den Heuvel, Edwin R.; Leenaars, Cathalijn H.C.; Burger, Huibert; Wiersma, Durk; Slooff, Cees J.; Knegtering, Henderikus; Bruggeman, Richard
Abstract: Altered emotional experiences in response to antipsychotics may increase the burden of disease in patients with schizophrenia. In a large cross-sectional study, patients with schizophrenia completed the Subjects Reaction to Antipsychotics questionnaire (SRA) to assess whether they attributed altered emotional experiences (flattened affect or depressive symptoms) to their antipsychotics. Association with antipsychotic D2 receptor affinity and occupancy was examined using logistic regression. We compared antipsychotic-attributed emotional experiences between patients using antipsychotic monotherapy and combination therapy. Of the 1298 included patients, 23% attributed flattened affect to their antipsychotics and 16% attributed depressive symptoms to their antipsychotics, based on the SRA. No differences were observed between antipsychotics in patients on monotherapy. We discuss that within these patients' relatively low dose range, altered emotional experiences did not appear to relate to the level of D2 receptor affinity of antipsychotic monotherapy. Patients using antipsychotic combination therapy (22%) were more likely to attribute depressive symptoms to their antipsychotics than patients using antipsychotic monotherapy (OR [95%CI]=1.443 [1.033–2.015]); possibly due to higher D2 receptor occupancies as estimated by dose equivalents. Highlights: Altered emotional experience to antipsychotics in with schizophrenia. Out of 1298 patients, 23% reported flattened affect and 16% depressive symptoms. We observed no difference between antipsychotics in patients on monotherapy.